Tinjauan Yuridis Restorative Justice pada Kasus Korupsi SPPD Fiktif KKR Aceh Ditinjau dari Undang-Undang Pemberantasan Tindak Pidana Korupsi - Richie Sanjaya Putra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research discusses the release of criminal sanctions in the SPPD KKR Aceh corruption case on the grounds that there is restorative justice at the police level because state losses have been returned. The resolution of corruption cases should refer to Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. This law has the principle of retributive justice and does not recognize restorative justice so that imposing criminal sanctions is the main option. 58 Actors who have authority because of their position have been proven to have committed corruption which is detrimental to state finances. On this basis, the 58 perpetrators should be given appropriate sanctions in Article 3 of Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes. This research uses a Juridical-Normative research method which is carried out by means of a literature study of available legal materials. This research method will be used to analyze sanctions against the 58 perpetrators of corruption in accordance with applicable positive law.